Integrated Thinking, Integrated Learning: Changing Our Ways for Changing Global Realities (LEARNing Landscapes, 2010)
The author strongly believes the complexity of our natural world and current societal issues cannot be addressed without interdisciplinary insights that can emerge only if formal education is allowed to go beyond the traditional silos of knowledge and practice. She describes how the Quebec Education Program, started 10 years ago, is based on competencies and integrated learning, thus transcending the boundaries between subjects. She discusses how Education Faculties have adapted to align teacher education with the current educational reform. Finally, she questions whether universities will be ready to receive this new generation of "transdisciplinary thinkers" who will soon be at their doors.
Keywords: education; knowledge; practice; interdisciplinary; Quebec; competencies; integrated learning; transdisciplinary thinkers; educational reform; teacher education